COVID-19, economic threat and identity status: Stability and change in prejudice against Chinese people within the Canadian population - Ferrante, Victoria Maria; Lacourse, Éric; Dorfman, Anna; Pelletier-Dumas, Mathieu; Lina, Jean-Marc; Stolle, Dietlind; de la Sablonnière, Roxane (Frontiers in Psychology, 2022)
Previous studies found a general increase in prejudice against Chinese people during the first months of the pandemic. The present study aims to consider inter-individual heterogeneity regarding prejudice and change involving Chinese people during the pandemic. The first objective is to describe different trajectories of prejudice. The second objective is to test the association between trajectories of prejudice and socio-demographic factors (age, gender, province of residence, political affiliation). The third objective is to examine if participants classified in different trajectories of prejudice differ in terms of economic threat and identity status (e.g., global identification). A representative Canadian sample (N = 3,617) was recruited for a 10-wave survey starting from April 2020. Four trajectories were identified. The first three trajectories have a low to very high level of prejudice against Chinese people. More than a quarter of the sample remains stable in their levels of prejudice, either very high (6.2% of the sample) or high (19.4%). A third trajectory (70.7%) reports low levels of prejudice that decrease very slightly over time. Finally, a fourth trajectory (3.7% of the sample) reports low levels of prejudice in favor of Chinese people, which become more positive throughout 2020 and slightly declines around December 2020. Some socio-demographic groups are associated with high or very high, stable trajectories of prejudice against Chinese people (e.g., “right-wing” political affiliation) while others are associated with the low, unstable trajectory of prejudice in favor of Chinese people (e.g., “left-wing” political affiliation). There was no significant difference between trajectories of prejudice regarding their levels of economic threat, but we found that high and very high stable trajectories of prejudice tend to favor a local strategy of identification comparatively to low unstable trajectories of prejudice which identify more globally. The present Canadian study shows that individuals differ in terms of both their level and change in prejudice against Chinese people throughout the pandemic with some socio-demographic groups being more likely than others to be associated with prejudice. The results also suggest that a promising way to tackle prejudice is to highlight a vision of the world where individuals are all “global citizens”.